Ponovna uporaba informacij javnega sektorja in vloga arhivistike - Merlak, Miha (Moderna arhivistika, 2022)
The purpose of the article is to find out what is the meaning of the re-use of information of the public sector, how the activity influences social and economic development and to find out Slovenia’s and the European Union’s view of the activity. The purpose is also to determine the role of archival science in the implementation of these processes.
Keywords: archival science; arhivistika; European Union; Evropska unija; information re-use; javni sektor; ponovna uporaba informacij; public sector